Prehospital pain treatment in children with burns - Skotnicka-Klonowicz, Grażyna; Grochocińska, Patrycja; Trambowicz, Kamil (Polish Journal of Public Health, 2012)
Introduction. Burns are one of the most serious children’s injuries. The most important activities in the scope of assistance for a child with burns include implementation of pain treatment in the prehospital period. Unfortunately, the level of understanding of the role of this treatment among doctors is not satisfactory.Aim. To evaluate the pain treatment in children with burns in prehospital period.Material and methods. Retrospective survey covered 193 burned children admitted to the Clinical Department of Emergency Medicine for Children in Łódź. The quality of pain treatment was analyzed on the basis of medical documentation.Results. In the studied group, the majority were boys (57.5%), and children below 4 years old (61%). Spilling hot liquid was the main cause of injury (81%). Burns covered mainly: neck/face – 36 children (17%), chest – 67 children (33%), upper limb – 60 children (29%); 75% burns were superficial. Painkillers were provided to 12 our of 23 children transported by medical rescue teams, 4 out of 20 children treated by family doctors, and 30 out of 150 children assisted by parents. The statistical analysis did not demonstrate significant differences between entities implementing pain treatment with regard to the number of children treated. Differences were observed in the case of medical rescue teams on the level p